Occurrence and Estimated Daily Intake of Cortisone and Cortisol in Aquatic Food from China TDS - Yi Yang; Jiachen Shi; Jie Yin; Yunjia Yang; Bing Shao; Jing Zhang (Foods, 2022)
Glucocorticoids (GCs) widely exist in animal food including aquatic food. This study aimed to survey the occurrences of cortisone and cortisol in aquatic food and the estimated daily intake (EDI) of cortisone and cortisol due to different habits of aquatic food consumption. The mean levels of cortisone and cortisol in freshwater fish purchased from market were 14.59 μg/kg and 69.15 μg/kg, respectively, which were markedly higher than the levels in marine fish. A test using Zebrafish was performed to compare the concentration of GCs by different killing methods. The results suggested that physically traumatic killing methods are one of the reasons why the levels of GCs in freshwater fish were higher than those in marine fish. The concentrations of cortisone and cortisol in composite aquatic food samples from 12 provincial districts of the fourth China Total Diet Study (TDS) were 0.72~15.75 μg/kg and 4.90~66.13 μg/kg, respectively, which were positively correlated with the distance from the coastline. Further, the correlation coefficient between the levels of cortisone and cortisol in aquatic food and the percentages of freshwater fish consumption were 0.758 (p < 0.01) and 0.908 (p < 0.01), respectively. There was a significant positive correlation between the levels of cortisone and cortisol in aquatic food in the fourth TDS and the percentages of freshwater fish consumption. The calculated average EDIs of cortisone and cortisol from aquatic food in the fourth TDS were 0.16 μg/d and 0.72 μg/d, respectively.